Thermodynamic Analysis of High‐Temperature Energy Storage Concepts Based on Liquid Metal Technology. Issue 3 (8th November 2019) - Laube, Tim; Marocco, Luca; Niedermeier, Klarissa; Pacio, Julio; Wetzel, Thomas
Abstract : Within the thermal energy storage (TES) initiative NAtional Demonstrator for IseNtropic Energy storage (NADINE), three projects have been conducted, each focusing on TES at different temperature levels. Herein, technical concepts for using liquid metal technology in innovative high‐temperature TES systems are dealt with. This approach implies some challenges; first, the unit costs are relatively large which makes a reduction of the mass inventory necessary. Second, the high thermal diffusivity, which is beneficial in any heat exchanger unit, reduces the efficiency in a single‐tank TES due to the fast degradation of the thermocline. These limitations can be overcome using a nonexpensive solid filler material, and, if properly designed, similar performance as in state‐of‐the‐art molten salt systems can be obtained, while maintaining the advantage of operating at temperatures well beyond their upper limit. Optimization strategies are presented for a reference case including transient behavior of the whole system. The sensitivity of multiple parameters, e.g., porosity, particle size, and influence of storage capacity regarding the discharge efficiency, is investigated. Abstract : Herein, technical concepts for using liquid metal technology in innovative high‐temperature thermal energy storage (TES) systems are dealt with. Optimization strategies are presented for a reference case including transient behavior of the whole system. The sensitivity of multiple parameters, e.g., porosity, particle size, and influence of storage capacity regarding the discharge efficiency, is investigated.